COMMUNITY-BASED WASTE SEGREGATION EDUCATION AND COMPOSTING INNOVATION USING THE OCTACO METHOD IN NALUK VILLAGE - Hanim, Wasifah; Aisha, Kayla Zeta; Jakti, Hilal Kuncoro; Helena, Fauziah Dwi; Shofia, Muthia Nur; Aura, Putri; Qhotimah, Yessika Siti; Ramadhani, Muhammad Raihan; Renaldi, Rafli; Sabina, Rahma Laila; Suparman, Siti Noorhuda (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Household waste management remains a critical environmental issue in Indonesia, particularly due to low public awareness of waste segregation practices. This community service program aimed to enhance the knowledge, awareness, and skills of residents in Naluk Village, Sumedang Regency, regarding waste separation and organic waste processing into compost using the OCTACO method. A qualitative and participatory approach was employed through observation, interviews, educational sessions, and hands-on composting demonstrations. The program was conducted over one month and involved local authorities, waste bank communities, and residents. The results indicate a significant improvement in participants’ understanding of waste classification and environmentally friendly waste management practices. The OCTACO composting method proved to be practical, odor-minimizing, and faster than conventional composting techniques. Overall, the program contributed to reducing household waste volume, strengthening environmental awareness, and promoting sustainable community-based waste management by transforming organic waste into valuable compost.